Vol.5 - "Stehir, Nico(ed.)" (London, 2005)
The concept of knowledge is one of the most widely used concepts in every day life, in scientific discourse and in reflections about science and technology. In these volumes editors defined five relevant areas for which they have sought contributions. These are (1) The Foundations of Knowledge; (2) Knowledge and Society; (3) Knowledge and the Economics;(4) Politics and Knowledge and (5) Sociology of Knowledge and science. The five areas are separated into five volumes of the current edition.
Keywords: Knowledge-Philosophical aspects